(untitled) (Bioagro, 2023)
The high content of antioxidants of maqui (Aristotelia chilensis (Mol.) Stuntz) has recently motivated an increase in the research on this species. This study evaluates the variation in phenolic antioxidants of maqui leaves in the Chilean province of Curicó according to geographical location and sun exposure, using total phenol content (TP) and specific leaf area (SLA) as indicators. Leaves were collected from natural populations inside the province, sampling 15 leaves and three replicates per geographic location. The relationships between SLA and TP, SLA and geographical location, and TP content and geographical location, were assessed in 20 locations within the province. TP varied from 118.36 to 201.9 mg∙g-1 (GAE) and SLA from 76.8 to 188.2 cm2∙g-1. In general, north facing plants exhibited the highest TP and the lowest SLA. When grouping sampled populations according exposure (north facing, south facing and valley), only north facing points resulted in a significant negative correlation with longitude (r= -0.980, P≤0.05), implicating that moving westward less phenol content would be found. TP and SLA varied according to exposure and geographical location. Correlation analysis revealed a significant negative relationship between SLA and TP (r = -0.56, P≤0.05), suggesting the use of this parameter as practical indicator of phenolic antioxidants in maqui.